Blood-Brain Barrier: More Contributor to Disruption of Central Nervous System Homeostasis Than Victim in Neurological Disorders - Xiao, Minjia; Xiao, Zhi Jie; Yang, Binbin; Lan, Ziwei; Fang, Fang (Frontiers in Neuroscience, 2020)
The blood-brain barrier (BBB) is a dynamic but solid shield in the cerebral microvascular system. It plays a pivotal role in maintaining central nervous system (CNS) homeostasis by regulating the exchange of materials between the circulation and the brain, and protects the neural tissue from neurotoxic components as well as pathogens. Here, we discuss the development of the BBB in physiological conditions and then focus on the role of the BBB in cerebrovascular disease, including acute ischemic stroke and intracerebral hemorrhage, and neurodegenerative disorders, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). Finally, we summarize recent advancements in the development of therapies targeting the BBB and outline future directions and outstanding questions in the field. We propose that BBB dysfunction not only results from but is causal in the pathogenesis of neurological disorders; the BBB is more a contributor to the disruption of CNS homeostasis than a victim in neurological disorders.